A Study of the Effectiveness of Total Quality Management in Different Industries - Faisal Imran; Rukhsana Chaudhary; Syed Kamran Dyder Sherazi; Kashif Lodhi (Social Science Review Archives, 2025)
This research analyzed the implementation of Total Quality Management (TQM) across the five key industrial sectors of Pakistan: the textile and pharmaceutical industries, the automotive and food processing sectors, and the telecommunications industry. Using a mixed-method research parse approach, TQM implementation across five industries carried out stratified sampling of 450 firms located in the major Pakistani cities of Karachi, Lahore, Islamabad, and Faisalabad. For the primary data, quality managers and production heads as well as senior level executives filled in structured questionnaires, while secondary data was collected from government publications as well as from the industry. Quality Management practitioners were the intended sample of the semi-structured interviews, 30 practitioners in all, and the purpose was to gather in-depth data regarding the implementation of TQM. There were cross industry variations which yielded different levels of effectiveness in TQM implementation, with the telecommunications and pharmaceutical industries having the best success and the food processing and textile industries falling behind in implementation. The major success factors which emerged were sustained leadership, employee training and active participation, focus on the customer, and a defined improvement framework. The most dominant finding was that organizations who embraced a more holistic approach to TQM were more effective in quality, customer satisfaction, operational productivity, and even more return on investment versus the less effective firms. There were a number of factors which inhibited effective implementation of TQM, as were reported in the more traditional sectors. These were: management unprepared to make a commitment, scarce resources, lack of training and a culture that was resistant to change." The study holds important implications for the Pakistani industry on the improvement of quality management practices, as well as suggesting a bespoke framework for the implementation for TQM on the regional industry.